Relevansi Teori Belajar Sosial Albert Bandura dan Metode Pendidikan Keluarga dalam Islam - Nurul Wahyuni; Wahidah Fitriani (Qalam : Jurnal Ilmu Kependidikan, 2022)
This study examines the relevance of Albert Bandura's social learning theory and family education methods in Islam. The problem is whether this social learning theory is in line with Islamic education methods in the family environment. This issue needs to be studied because this theory is hot in education in Indonesia and the family is the closest social environment to a child's life. Besides that, the facts show that education taught by parents is the initial foundation for the success of children's education in the future. Then, education in the family is the main key in forming the character and personality of children. This research is a library research using a qualitative approach. Data is collected through analysis of books and journals that are relevant to the problem. The data analysis technique used is the Miles and Huberman data analysis technique which consists of data reduction, data presentation and drawing conclusions. At the data reduction stage the writer will sort the data according to the research study which is then presented in words to produce new findings. Then the authors formulate conclusions as verification of research findings. Based on the results of the study it was found that Albert Bandura's social learning theory is relevant to the family education method in Islam. This can be seen from 1) Albert Bandura's social learning theory can be used in family education, 2) social learning theory is in line with the exemplary and habituation methods taught by Islam, 3) there is a process of observational learning and modeling which requires repetition in its application which is also used in the method family education in Islam. Kata kunci: Relevansi, Teori Belajar, Pendidikan Islam